Angiopoietin 1 and integrin beta 1b are vital for zebrafish brain development - Chen, Yu-Chia; Martins, Tomás A.; Marchica, Valentina; Panula, Pertti (Frontiers in Cellular Neuroscience, 2024)
Angiopoietin 1 (angpt1) is essential for angiogenesis. However, its role in neurogenesis is largely undiscovered. This study aimed to identify the role of angpt1 in brain development, the mode of action of angpt1, and its prime targets in the zebrafish brain. We investigated the effects of embryonic brain angiogenesis and neural development using qPCR, in situ hybridization, microangiography, retrograde labeling, and immunostaining in the angpt1 sa14264 , itgb1b mi371 , tek hu1667 mutant fish and transgenic overexpression of angpt1 in the zebrafish larval brains. We showed the co-localization of angpt1 with notch, delta, and nestin in the proliferation zone in the larval brain. Additionally, lack of angpt1 was associated with downregulation of TEK tyrosine kinase, endothelial (tek), and several neurogenic factors despite upregulation of integrin beta 1b (itgb1b), angpt2a, vascular endothelial growth factor aa (vegfaa), and glial markers. We further demonstrated that the targeted angpt1 sa14264 and itgb1b mi371 mutant fish showed severely irregular cerebrovascular development, aberrant hindbrain patterning, expansion of the radial glial progenitors, downregulation of cell proliferation, deficiencies of dopaminergic, histaminergic, and GABAergic populations in the caudal hypothalamus. In contrast to angpt1 sa14264 and itgb1b mi371 mutants, the tek hu1667 mutant fish regularly grew with no apparent phenotypes. Notably, the neural-specific angpt1 overexpression driven by the elavl3 (HuC) promoter significantly increased cell proliferation and neuronal progenitor cells but decreased GABAergic neurons, and this neurogenic activity was independent of its typical receptor tek. Our results prove that angpt1 and itgb1b, besides regulating vascular development, act as a neurogenic factor via notch and wnt signaling pathways in the neural proliferation zone in the developing brain, indicating a novel role of dual regulation of angpt1 in embryonic neurogenesis that supports the concept of angiopoietinbased therapeutics in neurological disorders.